Democratic protest - García Ruiz, Alicia (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: In this article, the idea of protest is approached along three dimensions. First, it deals with the relationship between protest and law (with particular attention to the problem of civil disobedience and the tension between legality and legitimacy). Secondly, the political role of social contestation in the functioning of democratic societies is addressed. Finally, the problem of punitive populism and repressive policies is analyzed in the context of societies strongly marked by inequality, poverty and social conflict